Evaluation of microbial contamination by Escherichia coli of cuts carcasses of broilers marketed in Tartous - نيصافي , علي; العمر, عبد الناصر; سليمان, شيم; عفيف, آلاء (Latakia University Journal -Biological Sciences Series, 2020)
coli is one of the most important pathogenic bacteria that causes bacterial contamination in poultry carcasses and it is important to find out contamination and determine the source of contamination, as well as determine the parts of the carcasses that are most exposed to contamination in some of the slaughtering and marketing stores in Tartous city. 150 samples of fresh chicken samples (25 heart samples, 25 liver samples, 25 breast meat samples, 25 breast meat samples, 25 thigh skin samples) were collected from different commercial shops in Tartous city for bacteriological examination. The results showed that aerobic plate count were (2.49×105- 4.37×105) CFU / g in breast and thigh meat respectively, (4.23 ×105 - 5.11 ×105) CFU / g in breast and thigh skin respectively, (3.25×105) CFU / g for liver samples and (3.89×105 )for heart samples.In addition, there were significant differences between the different parts, and the breast meat was significant over estimate other parts with a very high statistical significance P<0.001. Escherichia coli was isolated with 40% , 44%, 48% , 52% , 56% and 60% in samples of breast meat , liver , heart , breast skin , thigh meat and thigh skin respectively. Which make it more important the necessity of paying attention to applying general hygiene and disinfection during the different stages of preparing and marketing the carcasses (from slaughtering, processing and selling), in addition to instructing and educating workers and consumers about the dangers from the arrival of Escherichia coli from contamination of broiler carcasses and it is important to get a healthy safe food.